VSphere Design best practices : apply industry-accepted best practices to design reliable high-performance datacenters for your business needs /: apply industry-accepted best practices to design reliable high-performance datacenters for your business needs. (2014) - Bolander, Brian; Kusek, Christopher
No abstract available